SENYAWA AKTIF ANTIMAKANDARI UMBI GADUNG (Dioscorea hispida Dennst) - Sri Rahayu Santi (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
Isolation and identification of active antifeedant compounds from gadung tuber (Dioscorea hispida Dennst)has been carried out. As much as 12.03 g of concentrated methanol extract was resulted from 5.0 kg dry gadung tuberthat was macerated using methanol. Further, this extract was partitioned with n-hexane to obtain 2 concentratedextracts in n-hexane and methanol. The result of antifeedant test showed that the methanol extract was more activethan the n-hexane extract.Separations of the methanol extract using column chromatography (stationary phase : silica gel 60, mobilephase : methanol-chloroform 6:5) resulted four fractions. The most active fraction, FA , showed 2 spots on the TLC,so it was separated using preparative TLC which resulted in 2 fractions (FA.1 and FA.2). The antifeedant activity ofFA.1 fraction was higher than FA.2 fraction and it gave only 1 spot on the TLCThe result of identification using phytochemical test and spectrophotometer analysis suggested that FA.1fraction was alkaloid compound whose maximum wave length was 277.1 nm and it contained N-H (3425.3 cm-1), CHaliphatic (2927.7 and 2854.5 cm-1), C=O (1735.8 cm-1), C-N (1110.9 cm-1) and N-C=O (621.9 cm-1).